LITERASI DIGITAL MELALUI SOSIALISASI PENGGUNAAN APLIKASI JMO UNTUK MONITORING SALDO JHT PEKERJA PT. HM SAMPOERNA - Imroatul Husna Anggraini; Kustini Kustini (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The digitalization of public services requires community readiness to utilize technology-based services effectively and independently. The Jamsostek Mobile (JMO) application is a digital service innovation developed by BPJS Ketenagakerjaan to facilitate participants’ access to membership information, particularly for monitoring Old Age Security (JHT) balances. However, in practice, obstacles in using the application are still found due to limited digital literacy, especially among middle-aged workers. This community service activity aims to improve workers’ digital literacy through socialization of JMO application usage. The activity was conducted through face-to-face and individual assistance at PT HM Sampoerna Plant Rungkut Surabaya and PT HM Sampoerna Plant Malang, involving a total of 920 workers. A descriptive qualitative method was employed with data collection techniques including observation, pretests, and posttests. The socialization activities covered assistance with application installation, account registration and activation, as well as hands-on practice in using the JHT balance checking feature directly on participants’ smartphones. The results show an improvement in participants’ understanding and ability to independently use the JMO application after the socialization. These findings indicate that digital literacy socialization plays an important role in bridging the gap between digital public service innovation and users’ actual capabilities. This activity contributes to supporting the optimization of employment social security services and highlights the importance of sustainable digital literacy programs to ensure inclusive digital public service transformation. ABSTRAK Digitalisasi pelayanan publik menuntut kesiapan masyarakat dalam memanfaatkan layanan berbasis teknologi secara efektif dan mandiri. Aplikasi Jamsostek Mobile (JMO) merupakan inovasi layanan digital yang dikembangkan oleh BPJS Ketenagakerjaan untuk memudahkan peserta dalam mengakses informasi kepesertaan, khususnya pengecekan saldo Jaminan Hari Tua (JHT). Namun, pada praktiknya masih ditemukan kendala penggunaan aplikasi yang disebabkan oleh keterbatasan literasi digital, terutama pada kelompok pekerja paruh baya. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan literasi digital pekerja melalui sosialisasi penggunaan aplikasi JMO. Kegiatan dilaksanakan secara tatap muka dan individual di PT HM Sampoerna Plant Rungkut Surabaya dan PT HM Sampoerna Plant Malang dengan melibatkan total 920 pekerja. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, pretest, dan posttest. Sosialisasi meliputi pendampingan instalasi aplikasi, pembuatan dan aktivasi akun, serta praktik penggunaan fitur pengecekan saldo JHT secara langsung menggunakan smartphone peserta. Hasil kegiatan menunjukkan adanya peningkatan pemahaman dan kemampuan peserta dalam menggunakan aplikasi JMO secara mandiri setelah sosialisasi dilakukan. Temuan ini menunjukkan bahwa sosialisasi literasi digital berperan penting dalam menjembatani kesenjangan antara inovasi pelayanan publik berbasis digital dan kemampuan pengguna, serta mendukung optimalisasi pemanfaatan layanan jaminan sosial ketenagakerjaan.